Development of a Hyperopia Animal Model Using Blue Light in Guinea Pigs - Yoo, Yung Ju; Hwang, Jeong-Min (Korean journal of ophthalmology, 2025)
Purpose: Although numerous studies have investigated the progression of myopia, a reliable animal model for hyperopia remains undeveloped. This study aimed to evaluate whether blue light exposure can suppress emmetropization in a manner comparable to lens-induced hyperopia, thereby facilitating the development of an experimental animal model of hyperopia.Methods: Five-day-old 24 guinea pigs were randomly assigned to four different experimental groups based on light exposure conditions. They were housed under a 12-hour light/dark cycle (lights on at 8 AM and off at 8 PM) and exposed to either white light (control) or blue light (460 ± 20 nm). To induce hyperopia, a custom-designed +10 diopters (D) lens was fabricated using a three-dimensional printer and securely attached to randomly selected one eye with hook-and-loop fasteners and tissue adhesive. Refractive errors, corneal curvature, and axial length were measured using streak retinoscopy and A-scan ultrasound, with repeated measurements to assess intereye deviation.Results: At the end of the treatment period of 6 weeks, guinea pigs reared under blue light with an attached +10 D lens exhibited a significantly greater hyperopic shift compared to those reared under blue light without the lens. In contrast, guinea pigs raised under white light underwent emmetropization regardless of +10 D lens attachment.Conclusions: Blue light exposure significantly suppressed emmetropization by inducing a marked hyperopic shift in guinea pigs, whereas white light conditions support normal emmetropization regardless of lens attachment. These findings suggest that blue light plays a crucial role in hyperopia induction and can be effectively utilized to establish a stable hyperopia animal model.